Design and realization of a multisamples rotating high cycle fatigue machine - Domenico Gentile; Massimo Martorelli (Fracture and Structural Integrity, 2012)
In this work the design and the technical characteristic of a Moore rotating bending machine are presented. The machine has been realized at the University of Cassino in order to run tests on multiple specimens at different temperature. The user can choose independently the load and the temperature for each specimen. The machine has been designed to produce in short time a several numbers of data of materials fatigue strength at low costs. The machine is in assembling step at the Laboratory of Industrial Design of the University of Cassino.